Let present age of women be x.
Then,Present age of her daughter be y.
According to the question,
Two years ago,
Woman age = x - 2
Her daughter age = y - 2
Woman was 7 times old as her daughter. [ Given ]
x - 2 = 7 ( y - 2 )
=> x - 2 = 7y - 14
=> x - 2 + 14 = 7y
=> x + 12 = 7y ....( i )
After Three years ,
Woman age = x + 3
Her daughter age = y + 3
she would be 4 times old as the girl. [ Given ]
x + 3 = 4 ( y + 3 )
=> x + 3 = 4y + 12
=> x = 4y + 12 - 3
=> x = 4y + 9....( ii (
Now,
★ Putting the value of x = 4y + 9 from equation ( ii ) in equation ( i ),we get
x + 12 = 7y
=> 4y + 9 + 12 = 7y
=> 21 = 7y - 4y
=> 21 = 3y
=> 3y = 21
=> y = 21/3
=> y = 7
And,
x = 4y + 9
★ Putting the value of y in equation ( ii ), we get
x = 4 × 7 + 9
x = 28 + 9
x = 37
Hence, the present age of women is 37 years and her daughter age is 7.